2022
DOI: 10.1002/oby.23305
|View full text |Cite
|
Sign up to set email alerts
|

Impact of training modes on fitness and body composition in women with obesity: A systematic review and meta‐analysis

Abstract: Objective This study aimed to assess the effectiveness of different exercise modalities and determine the optimal exercise prescription for improving cardiorespiratory fitness, body composition, and metabolic health of women with obesity. Methods A systematic review of randomized controlled trials (RCTs) published between January 1988 and October 2020 was conducted. The RCTs were screened using the following inclusion criteria: 1) participants: women aged 18 to 65 years with BMI > 30 kg/m2 and without comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 94 publications
2
10
0
2
Order By: Relevance
“…In addition, our study shows different results from previous studies due to the inclusion of COM-HI motion mode. In their study, Pedro et al mentioned that resistance training combined with aerobic training had a -3.8% reduction in fat%, 95% CL: [-4.7, -2.9][71], and in Mary E et al's study, resistance training had the greatest effect on fat% reduction, -1.4%, 95% CL: [-4.24, 1.44] [72]. But our study found that COM-HI was perhaps the best exercise intervention for reducing P r e p r i n t fat%: -4.7%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study shows different results from previous studies due to the inclusion of COM-HI motion mode. In their study, Pedro et al mentioned that resistance training combined with aerobic training had a -3.8% reduction in fat%, 95% CL: [-4.7, -2.9][71], and in Mary E et al's study, resistance training had the greatest effect on fat% reduction, -1.4%, 95% CL: [-4.24, 1.44] [72]. But our study found that COM-HI was perhaps the best exercise intervention for reducing P r e p r i n t fat%: -4.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Data also revealed that, despite the lack of any significant difference in BMI between boys and girls, boys were more enduring, stronger, less fat, and less flexible than girls. According to Davis et al ( 43 ), three physiological factors may explain these differences. First, although girls tend to store more total body fat and subcutaneous fat, they oxidize fat more than carbohydrates during endurance and high-intensity exercise due to differences in muscle fiber typology (i.e., the ratio of type I to type II fibers).…”
Section: Discussionmentioning
confidence: 99%
“…This allows girls to have less adaptive stimulus to physical activity, who tend to experience smaller relative gains and adjustments than boys in response to chronic exercise, despite equal workloads ( 45 ). Not surprisingly, girls, regardless of BMI, tend to have lower levels of fitness than their male counterparts ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in most of the studies included in this systematic review no changes were found. The magnitude of changes in body composition depend on various factors, such as the type of intervention [55], the severity of hypoxic dose (i.e., %FiO 2 and duration) [52], the level of physical activity and the nutritional intake of the participants [56], in addition to the individual adaptive response [52]. These issues have not been carefully reported or controlled in any of the abovementioned studies, suggesting their possible influence.…”
Section: Effects Of Ih On Body Composition and Metabolic Parametersmentioning
confidence: 99%